内容发布更新时间 : 2025/2/2 11:09:33星期一 下面是文章的全部内容请认真阅读。
4+x=7 x+6=9 4+x=7+5
4+x-2=7 x-6=9 17-x=9
x-6=9+3 9+3=17-x 16+2x =24+x
4x=16
24-x =15+2x
3(x+6) =2+5x
2(x+4) -3=2+5x
20x-50=50
15=3x 2+5x=18+3x 2(2x-1)=3x+10 100-3(2x-1)=3-4x 28+6 x =88 1
4x+2=18 6x-2=3x+10 30-4(x-5)=2x-16 30+4(x-5)=2x-26 32-22 x =10
24-3 x =3 10 x ×(5+1)=60 99 x =100- x
36÷ x=18 x÷6=12 56-2 x =20
36÷ x-2=16 x÷6+3=9 56-3x =20-x
4y+2=6
16+8x=40
8x-3x=105
2(x+3)+3=13
56x-50x=30
32y-29y=3
x+32=76 2x-8=8 x-6×5=42+2x 12x-9x=9 5x=15(x-5) 5(x+5)=15 2
3x+6=18 4x-3×9=29 2x+5=7 × 3 6x+18=48 78-5x=28 89 – 9x =80
100-20x=20+30x 55x-25x=60 76y÷ 76=1
23y÷ 23=23 4x-20=0 80y+20=100-20y
53x-90=16 2x+9x=11 12(y-1)=24 80÷ 5x=100
19y+y=40
42x+28x=140
80y-90=70÷ 30
9÷ (4x)=1
51y-y=100
7x÷ 8=14 25-5x=15 3x-1=8-2x 78y+2y=160 20x=40 – 10x 85y+1=y+86 3
65x+35=100 79y+y=80 90y-90=90-90y 88-4x=80-2x 65y-30=100 45x-50=40-45x